Sidereal Astrology in Medieval Europe (Twelfth and Thirteenth Centuries): Traces of a Forgotten Tradition - Nothaft, C. Philipp E. (International journal of divination and prognostication, 2021)
Sets of astronomical tables available in Latin Europe during the Middle Ages can be classified based on whether they imitated Ptolemy in using a tropical zodiac for displaying planetary mean motions or followed an Indian tradition of preferring a sidereal reference frame. While this basic bifurcation in medieval computational astronomy is well known to modern scholars, there has so far been no systematic research concerning its consequences for the practice of astrology in this period. This article makes a first step by documenting cases from the twelfth and thirteenth centuries where Latin astrologers employed the sidereal zodiac for their calculations or expressly recommended its use for astrological purposes. Basing itself on printed sources as well as unpublished manuscript material, it provides evidence that a commitment to sidereal coordinates united several important figures during the early phases of the assimilation of Islamic mathematical astronomy in Latin Europe, but largely disappeared after 1250. As will be argued in the conclusion, this move away from sidereal astrology may possibly be linked to the thirteenth-century emergence of Paris as a major European center for the study of astrology.